COGEVIS: A New Scale to Evaluate Cognition in Patients with Visual Deficiency - Claire Meyniel; Dalila Samri; Farah Stefano; Joel Crevoisier; Florence Bonté; Raffaella Migliaccio; Laure Delaby; Anne Bertrand; Marie Odile Habert; Bruno Dubois; Bahram Bodaghi; Stéphane Epelbaum (Behavioural Neurology)
We evaluated the cognitive status of visually impaired patients referred to low vision rehabilitation (LVR) based on a standard cognitive battery and a new evaluation tool, named the COGEVIS, which can be used to assess patients with severe visual deficits. We studied patients aged 60 and above, referred to the LVR Hospital in Paris. Neurological and cognitive evaluations were performed in an expert memory center. Thirty-eight individuals, 17 women and 21 men with a mean age of 70.3 ± 1.3 years and a mean visual acuity of 0.12 ± 0.02, were recruited over a one-year period. Sixty-three percent of participants had normal cognitive status. Cognitive impairment was diagnosed in 37.5% of participants. The COGEVIS score cutoff point to screen for cognitive impairment was 24 (maximum score of 30) with a sensitivity of 66.7% and a specificity of 95%. Evaluation following 4 months of visual rehabilitation showed an improvement of Instrumental Activities of Daily Living (p=0.004), National Eye Institute Visual Functioning Questionnaire (p=0.035), and Montgomery–Åsberg Depression Rating Scale (p=0.037). This study introduces a new short test to screen for cognitive impairment in visually impaired patients.